REVISED STRUCTURES FOR TU 1718B AND VALCLAVAM - Baldwin, J; Claridge, T; Goh, K; Keeping, J; Schofield, C (1993)
The structures of Tü 1718B and valclavam, antibiotics produced by Streptomyces antibioticus ssp. antibioticus Tü 1718, have been reassigned as valyl-β,δ-dihydroxylysine (4) and the clavam (5) respectively, on the basis of NMR experiments and the observation that the former is a degradation product of the latter. © 1993.